The Social Interaction Patterns of Street Vendors in the Digulis Area of Pontianak within George Simmel's Framework - Babaro, Yolenta Stevani; Manalu, Esterrita; Pratama, Selvina; Nurwahid, Habib; Budiharto, Sutoyo (Jurnal Pendidikan Sosiologi dan Humaniora, 2025)
The existence of street vendors (PKL) has become a continually relevant topic of discussion over time. Street vendors are often perceived as a social problem within community structures. On the other hand, their presence significantly contributes to the circulation of the local economy. This study aims to identify the social interaction patterns of street vendors in the Digulis Area of Pontianak. The research employs a qualitative approach with a descriptive qualitative method. The sampling technique used is purposive sampling, while data collection was conducted through semi-structured interviews. The instruments used for data collection include observation sheets and interview guidelines, which were designed based on George Simmel’s theory. Data analysis techniques employed in this study are data reduction, data presentation, and conclusion drawing/verification as proposed by Miles and Huberman. The results show that the social interactions among street vendors in the Digulis Area of Pontianak occur in a harmonious and dynamic manner. Conflicts rarely occur due to collective awareness of maintaining harmony, while competition still exists but takes place in a healthy way. In addition, cooperation and social exchange are evident through practices of mutual assistance, borrowing trading materials, and sharing information among vendors. The form of social domination that emerges is economic in nature and is accepted reasonably, as it is perceived as a result of each vendor’s strategy and hard work. Overall, the social interaction patterns of street vendors reflect a balance between cooperation, competition, exchange, conflict, and domination as described by George Simmel.